Pengaruh Sistem Informasi Manajemen Terhadap Kinerja Karyawan Pada PT. Arta Boga Cemerlang Cabang Cirebon - Zuki Kurniawan (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2020)
Performance as an ability that a person has includes knowledge and skills. In the world of work, performance is the capacity that exists in a person to fulfill his work responsibilities so as to produce good output. The employee's performance will be said to be successful and optimal if it is in accordance with the company's desired results. The need for information systems to produce optimal employee performance is needed by computers based on Information Technology (computerization), so that it is not only able to optimize employee performance but also facilitate decision making for management because the data and information produced are fast and accurate. To find out the influence of management information system on employee performance, research was made. Thepurpose of this study is to analyze and test the influence of management information system on employee performance. In this study the population is PT Arta Boga Cemerlang Cirebon Branch,Jln. Nyi Gede Cangkring No. 99. To make it easier, save time, effort and cost, the researchers determined the size of the sample based on the Slovin formula. The sample obtained was 55 employees. Data analysis tools used in this study are validity and reliability test, significance test (t test), product moment correlation test (r test), determination coefficient (R2),and linear regression. From this research, it can be concluded that there is a positive and significantinfluence between management information system and employee performance, this can be seen from the results of the study showed a correlation of 0.68 and t calculate = 6,75. From the calculation result t calculate greater than t table which is 6.75 > 2.021; thus Ho hypothesis is rejected and ha alternative hypothesis accepted, i.e. there is a significant influence between management information system on employee performance. The coefficient value of determination of 0.46 or 46%,means that the variation in employee performance change(Y) is influenced by management information system (X) by 46%and the remaining 54%isinfluenced by other factors that are not calculated. Regression test results showed that management information system variables had a positive effect on employee performance with a coefficient of0.96. Performance as an ability that a person has includes knowledge and skills. In the world of work, performance is the capacity that exists in a person to fulfill his work responsibilities so as to produce good output. The employee's performance will be said to be successful and optimal if it is in accordance with the company's desired results. The need for information systems to produce optimal employee performance is needed by computers based on Information Technology (computerization), so that it is not only able to optimize employee performance but also facilitate decision making for management because the data and information produced are fast and accurate. To find out the influence of management information system on employee performance, research was made. Thepurpose of this study is to analyze and test the influence of management information system on employee performance. In this study the population is PT Arta Boga Cemerlang Cirebon Branch,Jln. Nyi Gede Cangkring No. 99. To make it easier, save time, effort and cost, the researchers determined the size of the sample based on the Slovin formula. The sample obtained was 55 employees. Data analysis tools used in this study are validity and reliability test, significance test (t test), product moment correlation test (r test), determination coefficient (R2),and linear regression. From this research, it can be concluded that there is a positive and significantinfluence between management information system and employee performance, this can be seen from the results of the study showed a correlation of 0.68 and t calculate = 6,75. From the calculation result t calculate greater than t table which is 6.75 > 2.021; thus Ho hypothesis is rejected and ha alternative hypothesis accepted, i.e. there is a significant influence between management information system on employee performance. The coefficient value of determination of 0.46 or 46%,means that the variation in employee performance change(Y) is influenced by management information system (X) by 46%and the remaining 54%isinfluenced by other factors that are not calculated. Regression test results showed that management information system variables had a positive effect on employee performance with a coefficient of0.96.